Experimental Solid Medium for Legionella Cultivation - L. S. Katunina; A. A. Kurilova; T. V. Taran; Yu. S. Kovtun; N. V. Churikova; A. A. Zuenko (Проблемы особо опасных инфекций, 2013)
Presented is the principal scheme for preparation of experimental medium for Legionella cultivation on the basis of fermentative hydrolysate of pig lung. Shown is that the culture medium has good growth properties and meets the requirements of regulatory documentation for culture medium used for isolation and cultivation of the causative agent of legionellosis.